1999
DOI: 10.1076/jcen.21.1.2.940
|View full text |Cite
|
Sign up to set email alerts
|

Wisconsin Card Sorting Test Performance Following Head Injury: Dorsolateral Fronto-Striatal Circuit Activity Predicts Perseveration

Abstract: The Wisconsin Card Sorting Test (WCST) has been argued to be a sensitive indicator of frontal lobe function. However, several recent studies have failed to find a consistent relationship between structural damage to this cortical area and perseveration on the test. In the present study, positron emission tomography (PET) imaging with 18F-fluorodeoxyglucose was used to examine the relationship of regional brain metabolism to perseverative responding on the WCST in patients with a history of closed-head injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(64 citation statements)
references
References 27 publications
2
60
0
2
Order By: Relevance
“…This suggests that the hippocampus is also sensitive to aging and may be involved in the cognitive processes engaged by the tasks used. This is not surprising given the importance of the hippocampus in learning and executive functions (Winocur and Moscovitch, 1990;Lombardi et al, 1999). The smaller HCV in the puppies indicates the hippocampus has not completely matured similar to the frontal lobes.…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that the hippocampus is also sensitive to aging and may be involved in the cognitive processes engaged by the tasks used. This is not surprising given the importance of the hippocampus in learning and executive functions (Winocur and Moscovitch, 1990;Lombardi et al, 1999). The smaller HCV in the puppies indicates the hippocampus has not completely matured similar to the frontal lobes.…”
Section: Discussionmentioning
confidence: 95%
“…In adults without primary psychiatric conditions, a positive relationship between executive function and caudate activity (Lombardi et al 1999;Volkow et al 1998) and volume (Fuh and Wang 1995;Mendez et al 1989) has been found. The present sample, however, included children prior to the age at which caudate volumes peak (Caviness et al 1996;Hardan et al 2003;McAlonan et al 2002;Thompson et al 2000).…”
Section: Caudate Volumes and Cognitive Performancementioning
confidence: 99%
“…Caudate nucleus lesions lead to impairments in planning and problem solving (Mendez et al 1989;Schmidtke et al 2002), mental flexibility (Lombardi et al 1999), learning (Poldrack et al 1999), attention (Mendez et al 1989), short-term and long-term memory (Fuh and Wang 1995), retrieval (Mendez et al 1989), and verbal fluency (Fuh and Wang 1995). Thus, the caudate may represent one underlying structural correlate of the cognitive deficits observed in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the paper and pencil version of Grant and Berg (1948) was used (see Heaton et al, 1993 andHeaton, 1981). Several studies have found that WCST performance activates the right dorsolateral frontal cortex (e.g., Berman et al, 1995;Lombardi et al, 1999;Riehemann et al, 2001). The dependent variable was the percentage of perseverative responses.…”
Section: Ef Tasks and Dependent Measuresmentioning
confidence: 99%